The role of translation loops in policy mutation processes: State designated Bioenergy Regions in Germany. (August 2017) - Albrecht, Moritz
The study is framed by EU renewable energy policy mobility and evaluates six German state-designated Bioenergy Regions and their role in policy performance processes. Based on in-depth interviews with Bioenergy Region personnel it displays aspects that shape the rationalities of actors and (re)produces policy translation and implementation. The cases are framed by a concept of translation loops and display the regions as relational assemblages that shape processes of policy mutation and influence the performance of policy aims. The paper shows how translation processes based on the socio-spatial relations of the involved entities affect initial policy aims and their implementations, particularly in regard to the prioritisation of economic aspects over sustainability. It further stresses the problem of insular approaches in bioenergy development that hinder joint approaches and problematises the questionable consequences of rationalist-linear based best-practice examples utilised in policy adjustment processes.